If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x-4)-7x=-5(-3x+2)
We move all terms to the left:
9(x-4)-7x-(-5(-3x+2))=0
We add all the numbers together, and all the variables
-7x+9(x-4)-(-5(-3x+2))=0
We multiply parentheses
-7x+9x-(-5(-3x+2))-36=0
We calculate terms in parentheses: -(-5(-3x+2)), so:We add all the numbers together, and all the variables
-5(-3x+2)
We multiply parentheses
15x-10
Back to the equation:
-(15x-10)
2x-(15x-10)-36=0
We get rid of parentheses
2x-15x+10-36=0
We add all the numbers together, and all the variables
-13x-26=0
We move all terms containing x to the left, all other terms to the right
-13x=26
x=26/-13
x=-2
| 7w+1=0 | | 3/16y=y/1+13 | | t+2.3/3=1.4 | | 5x–5=3x–9S | | k/3+5.44=8.48 | | 11x+7=150 | | h/3-15.7=-13.89 | | -20=-4v+2(v-6) | | 2.71(q+1)=8.13 | | 9.1=1.3(p+2) | | 15x-8=-3 | | 5(k-63)=90 | | 15x-11x=17+5–2 | | 4-4x=-2x-2 | | n+5+6n=-23 | | 3×1.5+11=4x1.5+1 | | 1/3m+7=-5 | | 7x+24=19x+23 | | 2t=4= | | (x+7)(x−3)=0 | | 5.4=8.9-0.5x | | -16+10=-3(x+6) | | 7x+15x=10 | | 7v-34=-9(v+2) | | 7−2p=3p | | |6a-5|=-4a | | w^2+(w+5)^2=12^2 | | 3(5x+5)=-40+25 | | .87=2x+x+2x+3 | | 0.833333333x+0.66666666=-9 | | -2(2s-4)-8=-2(5s+8)-3 | | -5x-5=-29 |